Edukasi Dan Latihan Teknik Back Pain Exercise Untuk Mencegah Nyeri Punggung Bawa Pada Nelayan Di Desa Tawiri - Mirdat Hitiyaut; Ernawati Hatuwe; Rahma Tunny; Syariefah Hidayati Waliulu; Siti Rochmaedah; Ira Sandy Tunny (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Low back pain (LBP) in Indonesia is a musculoskeletal complaint in the lumbar segment of the spine. One of the factors that influence complaints of low back pain (LBP) is work factors such as work position, work period, workplace design and body posture as well as body movement factors. Repetitive work, inefficient use of energy, long hours of work, unergonomic work positions and heavy workloads cause the incidence of LBP to increase. Therefore, it is necessary to increase insight into LBP as a promotive and preventive effort in reducing LBP symptoms. The methods used are counseling and leaflets as output results. There is a difference in understanding from the community and fishermen that after participating in this outreach activity, those who previously did not understand LBP disorders now understand more about what it is, the signs and symptoms, causes, intervention and prevention of LBP.